2018–2019 Florida Citrus Production Guide: Useful Telephone Numbers - Frederick M. Fishel (EDIS, 2019)
This 1-page fact sheet is part of the 2018–2019 Florida Citrus Production Guide. Written by Frederick M. Fishel and published by the Agronomy Department, January 2019.